Nephroprotective Effect of Herbal Extracts of Bryophyllum calycium and Solanum xanthocarpum on Induced Urolithiaisis in Wistar Rats: Haemato-Biochemical Evaluation - Patel, Daval B; Raval, SK; Mandali, GC; Patel, AC; Pande, AM (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The experiment was conducted on 90 adult healthy Wistar rats. Rats were randomly divided in to 15 equal groups, each of 6 rats, and were kept in separate cages. Group I served as normal healthy control without any treatment, while Group II & III served as vehicle (bicarbonate) control and lithiatic control, respectively. In rats of Group III to IX urolithiasis was induced using 0.75 % (v/v) ethylene glycol and 2% (w/v) ammonium chloride in drinking water for 28 days. The rats of Group I, II, and X to XV were given pure wholesome water till 28 days. After 28th day, the rats of urolithiatic treatment Groups IV, V, VI, VII, VIII and IX were given aqueous and alcoholic extracts of Bryophyllum calycium and Solanum xanthocarpum @ 300 mg/kg bwt orally as either single extract or combination as biherbal extracts in 0.5 % sodium bicarbonate using syringe and rat lavage needle, and so also was done for rats of Group X to XV as extract control groups. Blood samples were collected twice: i.e. on day 28 of induction of urolithiasis and then on day 56 of experiment from all rats. No significant difference was observed in any of the haematological parameters and even in serum albumin and globulin levels before and after treatment in different groups. However, increased levels of serum BUN, uric acid and creatinine were observed in the urolithiatic groups as compared to the normal control group on 28th day. While serum total protein levels were decreased in the calculi induced groups as compared to the normal control group. However, co-treatment of aqueous or alcoholic extract of Bryophyllum calycinum and Solanum xanthocarpum significantly restored these changes by 56th day. The effect of biherbal alcoholic extract of the plants was much better in restoring the values and the levels came nearer to normal by 56th day of oral treatment proving nephroprotective effect of these extracts.